Bamboo-like multiwalled carbon nanotubes dispersed in double stranded calf-thymus DNA as a new analytical platform for building layer-by-layer based biosensors - Primo, Emiliano Nicolás (2015)
This work reports the successful application of bamboo-like multiwalled carbon nanotubes (bCNT) non-covalently functionalized with calf-thymus double stranded DNA (dsDNA) as a robust platform (bCNT-dsDNA) to build electrochemical biosensors. The “model system” proposed here as a proof of concept was an enzymatic biosensor devoted to glucose quantification obtained by layer-by-layer self-assemby of polydiallyldimethylammonium (PDDA) and glucose oxidase (GOx) at glassy carbon electrodes (GCE) modified with bCNT-dsDNA (GCE/bCNT-dsDNA/(PDDA/GOx)n). The influence of GOx and PDDA assembling conditions and the effect of the number of PDDA/GOx bilayers (n) on the performance of the resulting biosensor is critically discussed. The supramolecular architecture was characterized by electrochemical impedance spectroscopy from the charge transfer resistance of quinone/hydroquinone and potassium ferrocyanide/potassium ferricyanide; by cyclic voltammetry from the surface concentration of GOx using ferrocene methanol as enzyme regenerator; by amperometry from the response of the enzymatically generated hydrogen peroxide; and by surface plasmon resonance from the changes in the plasmon resonance angle. The analytical parameters obtained with GCE/bCNT-dsDNA/(PDDA/GOx)3 for the amperometric quantification of glucose at 0.700 V were: sensitivity of (265 ± 7) μA mM−1 cm−2, linear range between 0.25 and 2.50 × 10−3 M, detection limit of 50 μM, repeatability of 3.6% (n = 10), and negligible interference from maltose, galactose, fructose and manose. The biosensor was successfully used for the sensitive quantification of glucose in beverages and a medicine sample.